What is the Role of Career Planning on Employee Performance - Ismawanti, Resty (Yayasan Pendidikan Belajar Berdikari, 2024)
Generally speaking, every business strives to raise worker productivity. The first step in advancing one's career is choosing a chosen path. Careful career planning is necessary to attain this development and the ability to handle obstacles properly. The purpose of this study is to assess how career planning affects PT Biofarma Area Bandung employees' performance. The 38 employees of the PT Biofarma Area Bandung Office make up the sample in this study, which uses multiple linear analysis as its methodology. The study's findings indicate that self-assurance and career planning together have a big impact on workers' output. Nevertheless, career planning had no discernible impact on worker performance at PT Biofarma Area Bandung when examined in isolation. It is therefore recommended that leaders at PT Biofarma Area Bandung give careful consideration to career planning elements, as this variable has a significant effect on worker performance. Goals of the company or organization can be met, and employee performance can be raised in this method